Risk factors for noncatheter-related Candida bloodstream infections in intensive care units: A multicenter case-control study - ERTÜRK ŞENGEL, BUKET; GÜL, FETHİ (OXFORD UNIV PRESS, 2019)
Candida bloodstream infections are associated with high mortality among critically ill patients in intensive care units (ICUs). Studies that explore the risk factors for candidemia may support better patient care in intensive care units. We conducted a retrospective, multicenter case-control study to investigate the risk factors for noncatheter-related Candida bloodstream infections (CBSI) in adult ICUs. Participants selected controls randomly on a 1:1 basis among all noncase patients stayed during the same period in ICUs. Data on 139 cases and 140 controls were deemed eligible. Among the controls, 69 patients died. The stratified Fine-Gray model was used to estimate the subdistribution Hazard ratios. The subdistribution hazards and 95% confidence intervals for final covariates were as follows: prior exposure to antimycotic agents, 2.21 (1.56-3.14); prior exposure to N-acetylcysteine, 0.11 (0.03-0.34) and prior surgical intervention, 1.26 (0.76-2.11). Of the patients, those exposed to antimycotic drugs, 87.1% (54/62) had breakthrough candidemia. Serious renal, hepatic, or hematologic side effects were comparable between patients those exposed and not-exposed to systemic antimycotic drugs. Untargeted administration of antimycotic drugs did not improve survival among candidemic patients (not-exposed, 63.6% [49/77]; exposed % 66.1 [41/62]; P = .899). This study documented that exposure to an antifungal agent is associated with increased the risk of subsequent development of CBSIs among nonneutropenic adult patients admitted to the ICU. Only two centers regularly prescribed N-acetylcysteine. Due to the limited number of subjects, we interpreted the positive effect of N-acetylcysteine on the absolute risk of CBSIs with caution.
Keywords: candidemia; Candida; intensive care units; case-control studies; risk factors; N-ACETYLCYSTEINE; SUBINHIBITORY CONCENTRATIONS; ALBICANS; FLUCONAZOLE; GLUTATHIONE; SUBDISTRIBUTION; MANAGEMENT; MODEL